Econometric Analysis of Producer Discount Policy - Błażejowski, Marcin (Eonometryczna analiza polityki rabatów cenowych, 2010)
In the paper we present econometric analysis of producer discount policy used by one of the Polish brewer companies. The range of analysis is limited by data availability and concerns such contractor characteristics like value of given discount, type of product, amount of order, distribution channel, region, market segment. An effort of reconstructing producer discount policy will be taken.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 91, s. 27-34
Keywords: sales modelling; econometric discount modelling; analysis of sales promotions